LAKE, THE REVISED ORDINANCES OF THE TOWN, ch. 32, §§ 1-9 (Beach, Barnard & Co. 1882). - (:unkn) unknown (General Publisher, 1882)
It shall be unlawful for any person within the limits of the town to carry or wear under his clothes, or concealed about his person, any pistol, colt or slung shot, cross knuckles, or knuckles of lead, brass or other metal, or bowie knife, dirk knife, or dirk, razor or dagger, or any other dangerous or deadly weapon.
--
Keywords: CARRY - CONCEALED